The Influence of Corporate Social Responsibility Disclosures on Investment Efficiency in the Asian Emerging Markets - Khuong, Nguyen Vinh; Herdianti, Fibi Rizki; Anh, Le Huu Tuan (UI Scholars Hub, 2022)
The aim of the research was to determine the efficiency of investing in companies that report on their corporate social responsibility (CSR) in developing markets. Companies that won the Asia Sustainability Reporting Awards 2020 were chosen for the study. We evaluate the correlation utilizing data from 36 firms from year observations of 2018 to 2020, using modified OLS estimation and regression analysis with modified panel data for heteroskedasticity and/or autocorrelation. In the emerging market, the sample period under examination is quite recent. Research findings show that CSR reporting has a significant negative effect on the company’s investment efficiency (IE) and that CSR reporting influences IE in the overinvestment scenario. The findings from this paper provide several implications for related parties and managers to enhance CSR disclosure and IE. They also contribute significantly to the existing literature about the relationship between CSR and IE when providing evidence from the ASEAN context.